Logistics in Argentina : Analysis, Options and Strategies to Overcome Emerging Restrictions - World Bank (Washington, DC, 2013)
In 2006 the World Bank wrote a report analyzing the situation of logistics in Argentina and identifying the main restrictions on trade flows. That report, entitled 'Argentina: the challenge of lowering logistics costs in the face of growth in foreign trade' was the first World Bank study designed to analyze the country's logistics performance. Based on the government's specific objective to achieve exports of US$60 billion by 2010, the report highlighted the need for significant improvement in the efficiency of transport networks and logistics services. In addition, the report underlined the risk of congestion at critical nodes that could develop if exports were to grow at the rate forecasted at that time (a rate that was in fact exceeded between 2006 and 2008, but which suffered a significant decline as from the crisis that began at the end of 2008). The high logistics costs faced by companies in the Argentine northwest (NOA) were also identified as a significant restriction in the 2006 report. This report makes a detailed analysis of the challenges and problems associated with the four topics identified in the preceding point, and presents recommendations of a general nature for their solution.